Knowledge, practices and associated factors regarding intravenous fluid electrolyte managements among Jimma University Medical Center Nurses, Southwest Ethiopia: Institution based Cross-Sectional study - Bashah Debrework Tesgera; Tesfamichael G/Mariam W/Mariam; Guba Dawud Kaweti; Jemberie Senetsehuf Melkamu; Addisu Taye Abate (International Journal of Africa Nursing Sciences, 2023)
Background: Understanding of fluid compartments within the body and how fluid moves between these compartments helps the nurses to make a competent assessment of fluid and electrolyte balance. Maintaining homeostasis in the body by correct fluid and electrolyte balance is one of the key issues extremely important for health. Objective: The study aimed to assess the nurses’ knowledge, practices and associated factors regarding intravenous fluid electrolyte managements at Jimma University Medical Center, Southwest Ethiopia, 2018. Methods: An Institution based Cross-Sectional study was conducted from March to May. 422 participants were randomly selected and data was collected using self-administered questionnaire. Data were analysed using the Statistical Package for Social Sciences (SPSS) version 20. The associated factors were identified using Binary and multiple logistic regression models. P-values < 0.05 were considered to be statistically significant. Result: The result showed that 59.6% and 88.3% of participants had adequate knowledge and good practice respectively. Professional attainment ((AOR = 2.561, 95% CI: 1.645–3.898)), experience ((AOR = 0.8.953, 95% CI: 2.399–33.410)) and respective unit/ward ((AOR = 2.092, 95% CI: 0.499–8.765)) were factors associated with knowledge. While education on intravenous fluid electrolyte (IVF) ((AOR = 3.748, 95% CI: 1.816–7.736)), presence of guide line in the unit ((AOR = 5.414, 95% CI: 1.889–15.518)), presence of fluid balance chart in the unit ((AOR = 3.412, 95% CI: 1.608–7.240)) and experience were associated with practice. Conclusion and recommendation: More than half and majority of respondents have had adequate knowledge good practice respectively. However, there is still knowledge and practice gap regarding intravenous fluid electrolyte managements. Therefore it is recommended to provide in service training and education for nurses.